Cell surface abnormality in clones of skin fibroblasts from a carrier of Duchenne muscular dystrophy. Issue 2 (April 1985) - Hillier, J; Jones, G E; Statham, H E; Witkowski, J A; Dubowitz, V
Abstract : We have previously reported that skin fibroblasts from patients with Duchenne muscular dystrophy (DMD) have a lower intercellular adhesiveness than control cells, and that cells from carriers of DMD have normal adhesiveness instead of the expected intermediate value. We have now cloned skin fibroblasts from a carrier of DMD (subject AS) who is also heterozygous for G6PD B/G6PD Mediterranean and determined the intercellular adhesiveness and G6PD phenotypes of the clones. G6PD activity was determined using the 2d-G6P/G6P ratio method. Normal cells had a percentage utilisation of 7.31% and uncloned cells from AS a value of 25.16%. Of 16 clones, 15 had normal values (mean 8.72%) while one clone was G6PD Med with a value of 57.5%. Mean intercellular adhesiveness of normal and uncloned cells from AS were 2.95 and 2.90 respectively. Of 11 clones tested, nine had normal values of adhesiveness (mean 3.1) and all these clones were G6PD B. The single G6PD Med clone had a value of 0.88, compared with 1.39 for DMD cells. We have no explanation at present for the single clone that was G6PD B but DMD-like on aggregation.